1997
DOI: 10.1016/s0885-3924(97)00081-x
|View full text |Cite
|
Sign up to set email alerts
|

Severe opioid toxicity and somatizationof psychosocial distress in a cancer patient with a background of chemical dependence

Abstract: A case of severe opioid toxicity is described in a 52-year-old cancer patient. The patient presented with classical clinical features of central hyperexcitability associated with opioid toxicity: delirium, myoclonus, hallucinations, hyperalgesia, and a possible seizure. This patient had a background of severe psychosocial distress and somatization in addition to a history of benzodiazepine dependence and alcohol abuse. The occurrence of opioid toxicity in this patient highlights the risks of a unidimensional a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 11 publications
1
38
1
Order By: Relevance
“…25 It has been suggested that patients with addictive disorders are at greater risk for somatization and chemical coping. 7,12,26,27 Our results showed that CAGEϩ patients presented to the PCC with higher symptom expression compared to CAGEϪ patients. Positive screening for alcoholism may function as a surrogate to detect a tendency to somatization.…”
Section: Alcoholism Screening In Patients With Advanced Cancer 965mentioning
confidence: 60%
See 1 more Smart Citation
“…25 It has been suggested that patients with addictive disorders are at greater risk for somatization and chemical coping. 7,12,26,27 Our results showed that CAGEϩ patients presented to the PCC with higher symptom expression compared to CAGEϪ patients. Positive screening for alcoholism may function as a surrogate to detect a tendency to somatization.…”
Section: Alcoholism Screening In Patients With Advanced Cancer 965mentioning
confidence: 60%
“…6 Some reports suggest that patients with a tendency to cope chemically express higher symptom distress. [7][8][9] Substance abuse including alcoholism are frequently underdiagnosed among cancer and palliative care patients. 10,11 Its detection is important because it has been described as a poor prognostic factor for cancer pain control.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the case of toxicity associated with chronic opioid use in cancer patients, the literature reports suggest a predominance of the hyperactive subtype or agitated delirium. [62][63][64][65] It is certainly possible that opioid-induced hypoactive delirium is underdiagnosed, especially when regular cognitive screening is not conducted. 66 Opioid-induced neurotoxicity has received increasing recognition in the last decade.…”
Section: Delirium and Cognitive Dysfunction: The Role Of Opioidsmentioning
confidence: 99%
“…108,109 The patient's agitation and the inability of staff to communicate with the patient can lead to a reflex response on the part of some physicians, who might resort to a prompt increase in opioid dose, which, in turn, could further aggravate the situation, especially if the opioid is already contributing to the delirium. 63 Cognitive impairment also introduces a major impediment to the process of patient counseling, often at a critical juncture in the cancer illness trajectory. 110 Inability of the cognitively impaired patient to give informed consent often hinders participation in research studies.…”
Section: Impact Of Opioid-associated Cognitive Effects On Patient Famentioning
confidence: 99%
“…3 The presence of alcoholism has been associated with poor pain control; patients who have a history of alcoholism are more susceptible to addiction and are poorly compliant with treatments. This group of patients is referred earlier to palliative care, expresses more symptom distress, and is more frequently on opioids.…”
Section: Introductionmentioning
confidence: 99%